California and other western wildfires - Seigel, Rachel (Disaster alert!, 2019)
Examines the disastrous effects, rescue missions, and aftermath of wildfires in the Western United States, specifically California and Canada. Discusses the role of climate change on wildfires and how people can prepare for fires in the future. Includes color photographs, a glossary, and further resources.